Development of label-free impedimetric platform based on new conductive polyaniline polymer and three-dimensional interdigitated electrode array for biosensor applications. (10th August 2015) - Voitechovič, E.; Bratov, A.; Abramova, N.; Razumienė, J.; Kirsanov, D.; Legin, A.; Lakshmi, D.; Piletsky, S.; Whitcombe, M.; Ivanova-Mitseva, P.K.
Graphical abstract: Abstract: Novel label-free impedimetric platform based on a three-dimensional interdigitated electrode array (3D-IDEA) sensor and new conductive polymer as a transducer for oxidoreductases is introduced. This platform is cost-effective, simple to construct and miniaturize. Monomer of conductive polymer N-(N', N'-diethyldithiocarbamoylethylamidoethyl) aniline (AnD) was deposited onto 3D-IDEA by chemical polymerisation. It was found that the polymer film resistance depends on the redox-potential of the solution. For the first time polyAnD was used as enzyme immobilisation matrix. Pyrroloquinolinequinone (PQQ) dependent alcohol and glucose dehydrogenases were immobilized on 3D-IDEA covered with polyAnD by two different methods. 3D-IDEA sensors with enzymes, which were immobilised by physisorption on polyAnD layer, showed specific response in the presence of 1 μM of the corresponding substrates. Obtained results revealed that PQQ dependent dehydrogenases can re-oxidize on polyAnD via direct electron transfer (DET) from enzyme active site to the polymer surface. This process can be monitored by methods of electrochemical impedance spectroscopy (EIS) and chronoamperometry. Presented study shows that EIS method gives a useful tool for research of re-oxidation process and interaction of electroactive enzymes with conducting materials giving information required to construct and develop analytical devices.